2018
DOI: 10.21577/0103-5053.20180155
|View full text |Cite
|
Sign up to set email alerts
|

Old Drawback on Azlactone Formation Revealed by a Combination of Theoretical and Experimental Studies

Abstract: New insights into the formation of azlactone heterocycles bearing different substituents are hereby presented. The sum of both kinetic and thermodynamic factors contributes for the formation of 2-alkyl or 2-aryl substituted azlactones, while the cyclization of 2-alcoxy azlactones is less favored. These results are in perfect accordance with experimental observations obtained by infrared (IR) and electrospray ionization mass spectrometry (ESI(+)-MS) of the crude reaction mixture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Hence, further experiments have been carried out, keeping in mind the importance of base choice in the coupling of N -Ac- l -phe. As previously mentioned, the racemization of amino acids occurs during the activation step, particularly in the cases of N -acetyl or N -benzoyl amino acids [ 28 , 29 ], and it is ascribed to the cyclization of the activated intermediate to give a heterocyclic azlactone ( L-3 in Figure 4 ). An intramolecular reaction between the oxygen at the acetyl N -protector group and the electrophilic site in C-1 promotes its formation [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, further experiments have been carried out, keeping in mind the importance of base choice in the coupling of N -Ac- l -phe. As previously mentioned, the racemization of amino acids occurs during the activation step, particularly in the cases of N -acetyl or N -benzoyl amino acids [ 28 , 29 ], and it is ascribed to the cyclization of the activated intermediate to give a heterocyclic azlactone ( L-3 in Figure 4 ). An intramolecular reaction between the oxygen at the acetyl N -protector group and the electrophilic site in C-1 promotes its formation [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…[22] This study showed that 2-aryl or 2-alkyl-substituted oxazolones are readily formed through the intramolecular cyclization of N-acyl amino acids, while the same process is less favored (due to a sum of both kinetic and thermodynamic factors) in carbamate protected amino acids. DFT (Density Functional Theory) calculations were performed in order to investigate the real role related to the synthesis of different 2-substituted azlactones.…”
Section: Nh][hsomentioning
confidence: 90%
“…Our research group recently reported a study involving the dimerization of azlactones (22) under Brønsted base catalysis. [28] Potassium or sodium trichloroacetate salts were employed as catalysts (30 mol-%) and the desired derivatives (23) were isolated in good to excellent yields (between 60 and 93 %) and with moderate to excellent diastereomeric ratio (up to > 19:1 d.r.)…”
Section: Other Ring-opening Reactionsmentioning
confidence: 99%
See 1 more Smart Citation